Antibody titers after a third dose of the SARS‐CoV‐2 BNT162b2 vaccine in immunocompromised adults in Greece: Is a fourth dose necessary?. Issue 10 (1st July 2022) - Kontopoulou, Konstantina; Nakas, Christos T.; Belai, Chrysoula; Papazisis, Georgios
Abstract: Real‐world data suggest that protection against COVID‐19 declines a few months after vaccination, particularly in the elderly and immunocompromised individuals. Our study aimed to analyze the humoral response induced by a third supplemental dose of BNT162b2 vaccine in a mixed group of immunocompromised individuals by determining anti‐spike (anti‐S) IgG antibody titers at baseline (pre‐third vaccine dose) and 4 weeks after the dose. Serum samples were obtained from a total group of 85 immunocompromised individuals (history of cancer: n  = 20, lymphoma: n  = 4, leukemia: n  = 3, transplant recipients: n  = 4, autoimmune disease: n  = 42, inflammatory disease: n  = 6, autoimmune diabetes type 1: n  = 6) all of whom had previously received a two‐dose schedule of the vaccine. The average number of days between second and third dose was 139.6145 (±41.39071). The overall IgG GMCs 4 weeks postvaccination were increased by more than 35 times (fold change = 35.30, p  < 0.001). Fold changes were not significantly correlated with underlying condition, age, sex nor with days between second and third dose. Considering the predominance of omicron variants in the current period and the results of studies showing a decrease in the effectiveness of the third dose after 10 weeks we highly recommend a fourth dose to this vulnerable population group.